A calibration framework for swarming ASVs' system design - Zainal Abidin, Zulkifli (NATL inst science communication-NISCAIR, 2012)
This paper is concerned with the virtual simulation of Autonomous Surface Vessels (ASVs) named, Drosobots, using virtual simulation software i. e. Webots™, and the pre-deployment in a swimming pool environment based on an improved simplest navigation technique. Swimming pool provides as a controlled calibration framework for the proposed swarming algorithm. The performance of the system is determined by firstly, its capability to allow the various robots to communicate amongst themselves in order to reach the desired location and secondly, the use of optimization in its searching strategy. By using basic theories of GPS steering, low-cost microcontroller and straightforward wireless communication method, a framework which takes into consideration both mechanical constraints in its physical setup and the suitability of control methods is presented. Swarming robots work as a team, propelled by slim-line water pump with cylindrical shape of body hull. In order to increase the robot's buoyancy, high density foam has been added to the previous design and results of the new rudder simulation effect is also been presented. Due to the delay of the NMEAs data and the limitation of an 8-bit micro-controller, complex control has been deferred until sometime in the future.